Giant Anal Fibroepithelial Polyp in a Healthy Teenage Boy: A Case Report and Literature Review. (1st June 2022) - Park, Kelley; Abbas, Paulette; Langenburg, Scott; Poulik, Janet; Hanan, Abdul; Shehata, Bahig M.
Abstract: Background: Fibroepithelial polyps of the anus have been described as mucosal hypertrophy in response to chronic irritation or tissue damage. Lesions usually remain small and mostly present in elderly adults with local disease. Case Report: An otherwise healthy 15-year-old male presented with a giant pedunculated mass projecting out of the anal verge that enlarged over 2 years, causing discomfort. Results: Upon surgical excision and histologic examination, the mass resembled a fibroepithelial polyp with numerous dilated lymphatics. Conclusions: While literature describes the spectrum of pathology possible in such lesions, often consisting of a mixture of stromal and epithelial components, dilated lymphatics are less common. This giant anal fibroepithelial polyp characterized by edematous stroma and numerous dilated lymphatics is consistent with lymphangioma. To our knowledge, this presentation is novel in this age group with no underlying risk factors.